(untitled) (Critical Journal of Social Sciences, 2026)
Donald Trump’s campaign playlists function as affective tools of temporal populism. Drawing on a dataset of 225 songs played at rallies between 2015 and 2024, the study combines computational analysis of audio features with cultural interpretation to examine how music shapes political memory and mobilization. Results reveal a marked preference for tracks from the 1970s and 1980s, characterized by high energy, emotional positivity (valence), and moderate acousticness. These sonic choices evoke a nostalgic affective climate aligned with the populist promise of national revival. Boxplots, ANOVA tests, and heatmaps show that genres such as rock, disco, and country dominate this curated soundscape, serving as emotional anchors for a narrative of decline and restoration. In this context, music performs affective temporal governance—organizing emotional experience across time through repetition, resonance, and embodied participation. Songs do not merely entertain; they act as scripts of belonging, instruments of soft power, and infrastructures of sonic memory. By collapsing temporal boundaries between past and present, Trump’s playlists orchestrate a politics of feeling in which nostalgia becomes a mobilizing force. The analysis contributes to the emerging field of sonic political analysis and underscores the role of music in shaping affective populism.